Improved glycemic control, pancreas protective and hepatoprotective effect by traditional poly-herbal formulation "Qurs Tabasheer" in streptozotocin induced diabetic rats - Ahmed Danish; Sharma Manju; Mukerjee Alok; Ramteke Pramod W; Kumar Vikas (BMC, 2013)
Abstract Background The present study was undertaken to evaluate the antihyperglycemic, antihyperlipidemic and hepatoprotective effect of a traditional unani formulation "Qurs Tabasheer" in streptozotocin (STZ) induced diabetic wistar rats. Up till now no study was undertaken to appraise the efficacy of "Qurs Tabasheer" in the diabetic rats. Qurs Tabasheer is a unani formulation restraining preparations from five various herbs namely Tukhme Khurfa (Portulaca oleracea seed), Gule Surkh (Rosa damascena flower), Gulnar (Punica granatum flower), Tabasheer (Bambusa arundinasia dried exudate on node), Tukhme Kahu (Lactuca sativa Linn seed). Methods Effect of Qurs Tabasheer was assessed in STZ (60 mg/kg, i.p single shot) induced diabetic wistar rats. STZ produced a marked increase in the serum glucose, Total Cholesterol, LDL cholesterol, VLDL Cholesterol, Triglycerides and trim down the HDL level. We have weighed up the effect of Qurs Tabasheer on hepatic activity through estimating levels of various liver enzymes viz. Hexokinase, Glucose-6-Phosphatase and Fructose-1-6-biphosphatase in STZ diabetic wistar rats. Results In STZ-induced diabetic wistar rats level of Hexokinase, and Glucose-6-Phosphatase was decreased to a significant level while the level of fructose-1-6-biphophatase was augmented. Therapy with Qurs Tabasheer for 28 days to STZ-induced diabetic rats significantly reduces the level of serum glucose, total cholesterol, triglycerides, glucose-6-phosphatase and fructose-1-6-biphosphatase, while magnitude of HDL cholesterol and hexokinase was amplified. Conclusion Antihyperglycemic, antihyperlipidemic activity of Qurs Tabasheer extract in STZ- induced wistar rats was found to be more effective than standard oral hypoglycemic drug Glimepiride.